2019
DOI: 10.2116/analsci.19p235
|View full text |Cite
|
Sign up to set email alerts
|

Critical Comparison of Reference Electrodes with Salt Bridges Contained in Nanoporous Glass with 5, 20, 50, and 100 nm Diameter Pores

Abstract: Porous glass frits are frequently used to contain the salt bridges through which reference electrodes interface samples. Prior work with widely used glass frits with 4-10 nm diameter pores showed that, when samples have a low electrolyte strength, electrostatic screening of sample ions by charged sites on the glass surface occurs. This creates an ion-specific phase-boundary potential at the interface between the sample and frit, and it biases the potential of the reference half-cell. Use of frits with much lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Moreover, the flow rate must be large enough so that components of the sample solution cannot diffuse against the fluid flow into the bridge electrolyte, as discussed previously. 19,20 The volume of solution that flows through a capillary over time (V/t) can be described with the following equation 34…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the flow rate must be large enough so that components of the sample solution cannot diffuse against the fluid flow into the bridge electrolyte, as discussed previously. 19,20 The volume of solution that flows through a capillary over time (V/t) can be described with the following equation 34…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To reduce such complications, porous frits, cracked glass junctions, fiber plugs, gels, or other methods of flow restriction can be used to inhibit the convective flow of the reference electrolyte into samples. , Indeed, for reference electrodes that comprise a nanoporous glass frit (4–100 nm pores), convective ion transport is a less efficient mode of mass transport than diffusion, resulting in the depletion of the electrolyte within the frit and sample components fouling the salt bridge. Such low flow rates and the ensuing contamination limit the use of low-flow salt bridges for long-term measurements. Evidently, the same problem also exists in the limiting case when the electrode design does not permit for solution flow at all, as it is the case for gel-filled systems. , On the contrary, increases in pore size to 500 nm and larger result in both large flow rates that require frequent replenishment of the bridge electrolyte and significant contamination of the samples with the bridge electrolyte …”
mentioning
confidence: 99%
“…Therefore, the same group carried out a methodical study to identify the optimum pore size between 1 and 100 nm . It was confirmed that the charge screening effect in solutions of low ionic strength occurs when the pore size is between 1 and 50 nm and does not occur when the pore size is 100 nm.…”
Section: Reference Electrodesmentioning
confidence: 88%
“…Therefore, the same group carried out a methodical study to identify the optimum pore size between 1 and 100 nm. 2 It was confirmed that the charge screening effect in solutions of low ionic strength occurs when the pore size is between 1 and 50 nm and does not occur when the pore size is 100 nm. Nevertheless, even frits with 100 nm pores should be used with caution because they will still be subjected to the above-mentioned convection driven uptake of the sample solution that can result in sample cross-contamination.…”
Section: ■ Reference Electrodesmentioning
confidence: 91%
“…To avoid sample-dependent liquid junctions at nanoporous frits, pore sizes less than 10 nm are recommended only for high ionic strength samples (where Debye lengths are smaller), while pores in the range of 1 µm are more suitable for low ionic strength solutions. 22 The latter do result in higher flow rates, though, and that can result in sample contamination when either very small samples are used or measurements are performed over longer periods of time.…”
Section: Flow-restricted Liquid Salt Bridgesmentioning
confidence: 99%